(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The article is devoted to discussing the ways certain major advantages in using folktales for teaching languages the meaning offolktales and the definition of critical thinking because folktales canhelp to develop children’s critical thinking and creative thinkingwhich are the most sophisticated things in learning foreign learning.